G270(P) Post-operative outcomes of gambian children and adolescents post valvular surgery for rheumatic heart disease. (12th March 2018) - Martin, K; Forrest, K; Jaiteh, L; Maane, R; Anderson, S
Abstract : Aims: Rheumatic heart disease (RHD) is a potentially debilitating and fatal condition with a high prevalence in low resource countries. The Gambia has many individuals with severe, symptomatic RHD but limited cardiology and no cardiothoracic surgical services. Charitable organisations fund surgery overseas for a minority. We aimed to review post-operative outcomes in this group. Methods: Paediatric RHD patients with documented pre- and post-operative management at our institution were included. Retrospective data from clinical records was collected on age, sex, HIV, HBV and sickle cell status, operation type, pre- and post-operative Ross scores and medication burden (table 1). For warfarinised patients, 'percentage days within therapeutic range' was calculated using the Rosendaal method. Results: 17 patients matched our inclusion criteria; 11 male, 6 female. Median age at surgery was 16 years. There was one death (cause: infective endocarditis). In total, 19 operations were performed involving 31 valve procedures; 7 metallic and 5 bioprosthetic valve replacements and 19 repairs. For the six warfarinised patients, median percentage days within target therapeutic range (TTR) was 40.2% and percentage of tests within TTR was 34.1%. Conclusion: In this small cohort of Gambian children and adolescents, cardiac surgery had a positive impact with significant effects on exercise tolerance and pill burden. Normal exercise tolerance following fifteen (78.9%) operations had positive social, economic and medical implications. However, there is a long-term risk of haemorrhage and thromboembolism in warfarinised patients given the low proportion of time in therapeutic range. Our evaluation highlights the challenges of working with adolescents around medication adherence, lack of alternatives to warfarin for young women of child bearing age and the need for high quality pre- and post-operative assessment and follow-up in low resource environments.